2020
DOI: 10.13106/jafeb.2020.vol7.no9.593
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Culture and Process in Mediating Human Capital Supply Chain on Firm Performance

Abstract: The purpose of this study is to examine and analyze the effect of human capital supply chain on the firm performance mediated by innovation culture and innovation process on small-and medium-sized construction enterprises (SMEs) in Indonesia. A survey has been distributed to all construction SMEs that have direct involvement in construction work (contractors and subcontractors). The construction SMEs including medium-and small-scale construction services in three Provinces, namely, the special region of Yogyak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 54 publications
1
41
0
1
Order By: Relevance
“…Research on medium-and smallscale companies found that innovation had a positive and significant impact on firm performance (Lestari et al, 2020). Other empirical evidence showed that innovation capability also had a positive relationship with firm performance (Hoang & Ngoc, 2019) and the innovation process also had a positive effect on firm performance (Muafi et al, 2020). Other research on medium-and small scale-companies showed that ambidextrous innovation had a significant effect on firm performance (Acosta, Popa, & Isabel, 2018).…”
Section: Ambidextrous Innovation and Firm Performancementioning
confidence: 99%
“…Research on medium-and smallscale companies found that innovation had a positive and significant impact on firm performance (Lestari et al, 2020). Other empirical evidence showed that innovation capability also had a positive relationship with firm performance (Hoang & Ngoc, 2019) and the innovation process also had a positive effect on firm performance (Muafi et al, 2020). Other research on medium-and small scale-companies showed that ambidextrous innovation had a significant effect on firm performance (Acosta, Popa, & Isabel, 2018).…”
Section: Ambidextrous Innovation and Firm Performancementioning
confidence: 99%
“…Corporate financial performance plays a key role in improving the quality of strategic decisions and ensuring the successful implementation of innovative strategies, including firm CSR [36], [37], [39], [40], [53]. Previous studies that examined the firm's financial performance showed that the firm's CSR can improve the firm's financial performance [54]- [56].…”
Section: Ceo Characteristics Quality Of Csr Disclosure and Financial ...mentioning
confidence: 99%
“…The results find that knowledge management in SC have many functions, including; (1) supply chain integration, (2) improvement of intra and inter-relationships throughout supply chain, (3) alignment of supply chain strategies and (4) strengthening knowledge transfer in product development. This proves SCM requires human resources role who have ability to manage SC properly and demanded to conduct the SCOL process sustainable and continuously (Muafi, Siswanti, Diharto & Salsabil, 2020). Muafi et al (2020) state that SC human capital has a very significant role in product and process innovation.…”
Section: H 1 Green Human Resource Management (Ghrm) Has a Significamentioning
confidence: 99%
“…This proves SCM requires human resources role who have ability to manage SC properly and demanded to conduct the SCOL process sustainable and continuously (Muafi, Siswanti, Diharto & Salsabil, 2020). Muafi et al (2020) state that SC human capital has a very significant role in product and process innovation. In the contingency approach, when an organization implements an innovation strategy, the company should implement an innovative SCOL.…”
Section: H 1 Green Human Resource Management (Ghrm) Has a Significamentioning
confidence: 99%
See 1 more Smart Citation